Dancing on My Own: Girls and Television of the Body. Issue 3 (November 2014) - Perkins, Claire
In all the critical hype around HBO's Girls (2012–), remarks on its intense physicality have been foremost — centering on Lena Dunham's blunt presentation of her 'imperfect' body in situations from sex to exercise to bathing to sleep. This article will consider the kinaesthetic affect of this, and other posing and performing bodies in Girls . Arguing that the choreographed body is central to the pleasures and accomplishments of the series as television, I suggest that its impact can be interpreted through the medium and art of dance.